Effective one-band models for the one-dimensional cuprate Ba2-xSrxCuO3+δ - Feiguin, A. E.; Helman, Christian; Aligia, Armando Ángel (American Physical Society, 2023)
Fil: Feiguin, A. E.. University Northeastern; Estados Unidos. Northeastern University; Estados Unidos